2022
DOI: 10.1186/s13102-022-00603-1
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle characteristics in adolescent female football players: data from the Karolinska football Injury Cohort

Abstract: Background Normative values of lifestyle characteristics in adolescent female football players may be used by clinicians and coaches to take actions because the potential important for well-being, performance on the pitch, and risk of injury. The aim was to report descriptive characteristics of lifestyle factors in adolescent female football players and potential changes over 1 year. Methods We included 419 adolescent competitive female football pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Dietary habits, energy intake, and metabolism were always clustered as one or more themes in performance studies, but there was also a strong presence of studies demonstrating a link between these themes and injury ( Cavarretta et al, 2018 ; Faltstrom et al, 2022 ). This cluster could be found in both periods, with the primary approach being the relationship to injury, which can be influenced by behaviors related to diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary habits, energy intake, and metabolism were always clustered as one or more themes in performance studies, but there was also a strong presence of studies demonstrating a link between these themes and injury ( Cavarretta et al, 2018 ; Faltstrom et al, 2022 ). This cluster could be found in both periods, with the primary approach being the relationship to injury, which can be influenced by behaviors related to diet.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, (Silva et al, 2017) reported that the interaction between a player's style of play and the surface condition of the turf may be a contributing factor to injury. Multiple studies have been published on the relationship between turf type and injury prevalence, as well as literature reviews and meta-analyses, and to date, research continues to be attempted (Calloway et al, 2019) Dietary habits, energy intake, and metabolism were always clustered as one or more themes in performance studies, but there was also a strong presence of studies demonstrating a link between these themes and injury (Cavarretta et al, 2018;Faltstrom et al, 2022). This cluster could be found in both periods, with the primary approach being the relationship to injury, which can be influenced by behaviors related to diet.…”
Section: Other Injurymentioning
confidence: 99%
“…Based on the results of previous studies, 14-16-year-old adolescents are at higher risk of developing the habit of smoking [34] and the co-occurrence of smoking and drinking [32,35]. A recent study conducted with adolescent female football players observed that few players used tobacco and alcohol, but drinking alcohol appeared to increase with age [36]. The results of the present work also highlight the problematic situation that 16-year-old athletes could be facing when it comes to alcohol and tobacco use.…”
Section: Discussionmentioning
confidence: 99%